Coherence Based Double Talk Detector with Adaptive Threshold - Tashev, Ivan (XX Scientific Conference ELECTRONICS ET2011, 2011)
Acoustic echo cancellation is one of the oldest applications of the adaptive filters and today part of each speakerphone. An important block of each acoustic echo canceller is the double talk detector. It blocks the adaptation of the filter when near end voice is present and thus preventing the adaptive filter from diverging from the optimal position. In this paper we present an improved version of coherence based double talk detector with improved precision compared to the base algorithm.